2000
DOI: 10.1083/jcb.150.5.1027
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Mitochondrial Structure and Function after Bid- or Bax-Mediated Cytochrome c Release

Abstract: Proapoptotic members of the Bcl-2 protein family, including Bid and Bax, can activate apoptosis by directly interacting with mitochondria to cause cytochrome c translocation from the intermembrane space into the cytoplasm, thereby triggering Apaf-1–mediated caspase activation. Under some circumstances, when caspase activation is blocked, cells can recover from cytochrome c translocation; this suggests that apoptotic mitochondria may not always suffer catastrophic damage arising from the process of cytochrome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
154
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(176 citation statements)
references
References 49 publications
(69 reference statements)
20
154
2
Order By: Relevance
“…37,38 The posttranslational import of nuclear-encoded proteins into mitochondria however is a vital, natural function of mitochondria. The work of von Ahsen et al 32 demonstrated that protein import was preserved after complete release of cytochrome c. This could be shown for isolated mitochondria from Xenopus oocytes and human HL-60 cells. Mitochondrial membrane potential was also maintained in apoptotic HeLa cells that were induced to undergo apoptosis by treatment with UV or staurosporine, provided that caspase activation was prevented by zVADfmk.…”
Section: Cytochrome C Release From Isolated Mitochondriamentioning
confidence: 77%
See 1 more Smart Citation
“…37,38 The posttranslational import of nuclear-encoded proteins into mitochondria however is a vital, natural function of mitochondria. The work of von Ahsen et al 32 demonstrated that protein import was preserved after complete release of cytochrome c. This could be shown for isolated mitochondria from Xenopus oocytes and human HL-60 cells. Mitochondrial membrane potential was also maintained in apoptotic HeLa cells that were induced to undergo apoptosis by treatment with UV or staurosporine, provided that caspase activation was prevented by zVADfmk.…”
Section: Cytochrome C Release From Isolated Mitochondriamentioning
confidence: 77%
“…31 Recently von Ahsen et al demonstrated that recombinant Bid and Bax can release cytochrome c from mitochondria without causing mitochondrial depolarization or inducing changes in mitochondrial ultrastructure. 32 Mitochondria that have lost their cytochrome c were shown to be in the same condensed conformation as control mitochondria. Electron microscopy as well as tomography 33 could not reveal any significant change in the ultrastructure.…”
Section: Cytochrome C Release From Isolated Mitochondriamentioning
confidence: 96%
“…However, electron microscopic tomography has shown that often the cristae are closely apposed, forming long channels between their outer faces with constrictions (cristae junctions) at the outer ends of the channels that seem to restrict movement of large solutes, including IMS proteins (20). The extent of constriction of IMS protein movement is not agreed by all researchers (21,22). The MPT pore, when opened, collapses all solute gradients, including those that generate mitochondrial bioenergetic function.…”
Section: Mitochondrial Changes At the Ultrastructural Levelmentioning
confidence: 92%
“…The plasmid was transformed into Escherichia coli BL21 and recombinant tBid was produced as described. 48 Cell permeabilization experiments Cells (6 Â 10 5 ) per well were seeded in six-well plates. The next day cells were washed twice with washing buffer containing 120 mM NaCl, 5 mM KCl, 1 mM KH 2 PO 4 , 0.2 mM MgCl 2 , 0.1 mM EGTA and 20 mM HEPESNaOH pH 7.4, and then incubated 10 min in permeabilization buffer containing 120 mM KCl, 10 mM NaCl, 1 mM KH 2 PO 4 , 20 mM HEPES-Tris pH 7.2, a protease inhibitor cocktail (Roche Diagnostic, GmbH, Mannheim, Germany), 100 mg/ml digitonin (Sigma), 2 mM succinate, 2 mM ATP, 5 mM phosphocreatine (Sigma) and 5 U/ml creatine phosphokinase (Sigma) at 371C in the presence or absence of 500 ng of recombinant tBid.…”
Section: Recombinant Tbidmentioning
confidence: 99%